Pengaruh strategi marketing gamifikasi dan neuromarketing melalui User Interface (UI) aplikasi terhadap loyalitas konsumen - Gifhary, Muhammad Naufal; Hermina, Nurul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Digitalization has brought great changes and affected people's activities, and the convenience provided by digitalization makes people switch to everything digital. The purpose of this study is to analyze the effect of gamification and neuromarketing marketing strategies through User Interface (UI) applications on consumer loyalty. The research method used is quantitative method. Based on the results of this study, it can be concluded that gamification and neuromarketing simultaneously have a significant effect on Shopee marketplace Consumer Loyalty. Neuromarketing partially has a positive and significant effect on Shopee marketplace Consumer Loyalty. Gamification partially has a positive and significant effect on Shopee marketplace Consumer Loyalty. Based on the research, it can be concluded that this research variable strengthens the existing theory in previous journals about the effect of gamification and neuromarketing on independent variables, especially consumer loyalty.